Analysis of Online Teaching At the Time of The Pandemic at Mi Miftahul Ulum Tongas - Imro Atus Soliha (Jurnal Teknologi Pembelajaran, 2022)
Abstract This study aims to analyze how the learning process during the COVID-19 pandemic is carried out on the network (Daring), and also review the factors in the learning process at MI (Madrasah Ibtidaiyah) Miftahul Ulum Tongas. This research was held in October 2020. The Researcher used qualitative research with phenomenological design. Questionnaires and interviews were used in collecting the data. The subjects used in the study were several teachers at MI Miftahul Ulum Tongas. The results of this study showed that learning at MI Miftahul Ulum using WhatsApp group application and google form. Offline learning is also applied while adhering to health protocols. The supporting factors of online learning at MI Miftahul Ulum Togas are gadgets, laptops, internet quotas, and books. While the inhibiting factors of online learning were: teachers can not explain maximally, motivation of learners, and economic factors.